1992
DOI: 10.1002/bies.950140208
|View full text |Cite
|
Sign up to set email alerts
|

The end of the message: 3'– end processing leading to polyadenylated messenger RNA

Abstract: Almost all messenger RNAs carry a polyadenylate tail that is added in a post-transcriptional reaction. In the nuclei of animal cells, the 3'-end of the RNA is formed by endonucleolytic cleavage of the primary transcript at the site of poly(A) addition, followed by the polymerisation of the tail. The reaction depends on specific RNA sequences upstream as well as downstream of the polyadenylation site. Cleavage and polyadenylation can be uncoupled in vitro. Polyadenylation is carried out by poly(A) polymerase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…This will permit stringent control of reaction conditions, concentrations of enzymes and substrates, and their order of addition. Only this, in turn, will permit the contributions of individual components and their interactions to be studied (71). To this end, we have purified, characterized, and molecularly cloned an ARE RNA-binding protein, AUFI, whose binding specificity suggests its involvement in ARE-directed mRNA degradation in cells.…”
Section: Discussionmentioning
confidence: 99%
“…This will permit stringent control of reaction conditions, concentrations of enzymes and substrates, and their order of addition. Only this, in turn, will permit the contributions of individual components and their interactions to be studied (71). To this end, we have purified, characterized, and molecularly cloned an ARE RNA-binding protein, AUFI, whose binding specificity suggests its involvement in ARE-directed mRNA degradation in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The S. dimidiatum I‐ Ppo I type endonuclease has no polyadenylation signal site (AAUAAA) at the 3′ end [32] and no product was visualized after RT‐PCR (primers 204L2/204R2; data not shown). We concluded that the I‐PpoI endonuclease type gene is not expressed in S. dimidiatum , contrary to Naegleria sp.…”
Section: Resultsmentioning
confidence: 99%
“…The insertion of endonuclease ORFs into peripheral loops maintains the ability of the intron to splice from the host gene, and preserves a functional 18S gene. His‐Cys homing endonucleases have been described in the rDNA group I introns [41] of the myxomycetes P. polycephalum [32] and Didymium iridis [35], the amoeboflagellate genus Naegleria [44], the ascomycete Beauveria bassiana [45], Nectria galligena [46], the zygomycete Coemansia mojavensis [47] and an ericoid fungal isolate PSIV [14]. Sequencing of the RT‐PCR product revealed in vivo co‐splicing of the IC1 intron containing the endonuclease gene without splicing intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…1). The conserved sequence (TTTTTT), which is one of several possible downstream signals required for efficient eukaryotic mRNA polyadenylation (20), was located in the 3Ј-NFR of the Ctpct gene, 50 bp downstream of the 3Ј-terminus of exon 9 (Fig. 4C).…”
Section: Figmentioning
confidence: 99%